Influencia de la calidad en la cobertura y el servicio de agua potable que brinda la empresa Emapa San Martín S.A. - Asmat Sigueñas, Esther (2010)
Water quality is a requirement of global markets, went to a trade pattern required by the development of quality criteria that value the man as a consumer par excellence, is one of the most sensitive issues in the provision of services sanitation. Poor water quality can have devastating effects on the population, which is why it is necessary to offer quality drinking water service to prevent any problems. Similarly, the professionals responsible for this task should be aware of existing legislation on water quality and its implementation, as well as techniques and procedures of treatment and control of water quality is subject to continuous improvement, which should be properly disseminated among the professionals responsible for this task. The commitment to improve the knowledge base on all aspects involving maintaining adequate levels of coverage and quality of drinking water service provided by the company EMAPA SAN MARTIN SA For that reason, the object of our research is aimed at studying "INFLUENCE OF THE COVERAGE AND QUALITY OF DRINKING WATER SERVICE COMPANY THAT OFFERS EMAPA SAN MARTIN SA The Company Municipal Potable Water Supply and Sewerage of San Martín, is a private law firm, subject to the laws of public internal control. Its administrative, technical and economic is subject to public control laws and the rules of sanitation. His goal is to provide water service to optimal levels of efficiency and safety to each and every one of the residents who live in their jurisdiction. This framed by the law of state enterprises, its regulations approved by DS N ° 23 853 Organic Law of Municipalities, General Corporation Law, Act No. 26 338 Sanitation Act and the regulations adopted to by DS No. 09-95-PRE, by the provisions of the Statute of the Company, as amended on December 28, 1999. EMAPA SAN MARTIN SA has a coverage of potable water household connections active to December 2009, according to the document management indicators 31.304 house connections and sewerage coverage of 26 531 for an estimated urban population of 169.339 inhabitants. Potable water production to that date was 1,091,388.00 m3 and Continuity of service 11.31 hours / day. There are several principles to be followed to carry out customer service, they can provide the vision that has about the most important aspect of the service, the customer. Make quality a habit and a framework, set specifications for the products and services in agreement with all staff and with customers and suppliers, anticipate and consistently meet customer needs, give freedom of action at all employees who have dealings with customers, ie authority to address their complaints, customers always expect the fulfillment of his word. Promise less, do more, to show respect for people and be attentive to them, explicitly acknowledge any effort of implementing a quality culture. Paying your employees as if they were his partners (incentives). Do as the Japanese. In other words, investigate who are the best and how they do things, to usurp their systems, then improve them. Quality service must meet the following characteristics: fulfill your goals. Serve for what it was designed, addressing the needs, provide results. The objective is to determine the level of influence of the coverage and quality of drinking water service provided by the company EMAPA SAN MARTIN SA to: • Know the procedure that follows the company for potable water coverage provided EMAPA SAN MARTIN SA • Develop strategies to quality and service coverage of drinking water provided by the company EMAPA SAN MARTIN SA to meet user requirements. • Suggest measures to reduce water loss in EMAPA SAN MARTIN SA It will use the following research methods: • Inductive Method. - This is the method of obtaining knowledge that leads from the particular to the general, the facts on the causes and the discovery of the laws. Such a method may be able to establish general laws from empirical facts. • Deductive Method. - Acquiring expertise of the company EMAPA through nationwide general situations. According to their application Application . It is concerned with collecting information from reality to enrich the scientific theoretical knowledge. We will obtain new knowledge about the quality of coverage and water service. According to the level of depth: Descriptive Research. As its name suggests describes situations and facts of how certain phenomena are manifested. It specifies the main characteristics of individuals or groups, phenomena that are tested. In this type of research is measured precisely as possible. It requires knowledge of the study area. Includes the account of the reality in terms of coverage of drinking water Company in the region of San Martín. The universe of the population is 34,000 users of the Municipal Water and Sewer and the sample was obtained according to the application of the formula of the cluster with the following results will be implemented structured survey to Tarapoto 200 120 Bellavista Lamas 20 Saposoa 20 and San José de Sisa 20 respectively.